THU0438 INADEQUATE CARE FOR PATIENTS HOSPITALISED WITH GOUT: EVIDENCE THAT EULAR GUIDANCE IS NOT UTILISED. (2nd June 2020) - Russell, M.; Clarke, B.; Rampes, S.; Dokal, K.; Mahto, A.; Rutherford, A.; Galloway, J.
Abstract : Background: Hospitalisations due to gout have increased over the last decade, in direct contrast to declining admissions for other inflammatory arthritides including RA [1]. Gout is a treatable condition with recently published EULAR guidelines [2, 3]. Admissions could be avoided with effective use of urate-lowering therapies (ULT). Objectives: We hypothesised that the majority of patients attending hospital with acute gout attacks would not be on ULT. Furthermore, we hypothesised that the majority of patients would not be provided with a plan for ULT commencement and/or uptitration on discharge, leaving them at risk of further hospitalisations. Methods: We retrospectively analysed electronic health records for all patients presenting acutely with a primary admission diagnosis of gout (ICD-10 code: M10) at two hospitals in London, UK, from January – December 2017. Analyses of in-hospital gout management were performed for these patients, including to ascertain the number and proportion of patients who: i) had a known history of gout; ii) were receiving ULT at time of attendance; iii) were provided with a discharge plan for ULT commencement and/or uptitration. Results: Over a 12-month period, there were 234 emergency attendances for gout in 225 individuals. 80% were male, with a mean age of 58 years. 70/234 (30%) attendances resulted in admission to hospital (mean length of stay: 2 days; range: 0-31 days). 211 patients had routinely captured clinical data available for further analysis. 90/211 (43%) patients had prior diagnoses of gout, of whom 38% were on ULT at presentation (32 allopurinol, 2 febuxostat). 38% of patients were discharged with a plan for ULT commencement and/or uptitration. 20 patients re-presented to hospital with acute gout within 12 months (17/20 were not receiving ULT). Conclusion: Most patients hospitalised with gout were not receiving ULT, even those with a prior history of gout attacks. Few were provided with a ULT plan, leaving them at risk of re-admission to hospital. Hospital admissions are unpleasant for patients and incur a high economic burden for health services; if they are to be prevented, there must be a concerted effort to implement and follow gout management guidelines to ensure patients receive ULT at appropriate doses. References: [1]Russell M, et al . Return of the King: Rising Incidence of Acute Hospital Admissions due to Gout. J Rheum 2019 Sep 15. [2]Richette P, et al. 2016 updated EULAR evidence-based recommendations for the management of gout. Ann Rheum Dis 2017;76:29-42. [3]Richette P, et al. 2018 updated European League Against Rheumatism evidence-based recommendations for the diagnosis of gout. Ann Rheum Dis 2020;79:31-38. Disclosure of Interests: None declared